66 MYOCARDIAL EDEMA CONTRIBUTES TO INTERSTITIAL EXPANSION AND ASSOCIATES WITH MECHANICAL AND ELECTROCARDIOGRAPHIC CHANGES IN TAKOTSUBO SYNDROME: A CMR T1 AND T2 MAPPING STUDY. (15th December 2022) - Arcari, Luca; Camastra, Giovanni; Ciolina, Federica; Limite, Luca Rosario; Danti, Massimiliano; Ansalone, Gerardo; Musumeci, Beatrice; Sclafani, Matteo; Sbarbati, Stefano; Cacciotti, Luca
Abstract: Background: myocardial edema has a central role in takotsubo syndrome (TTS). Relationships between edema, mechanical and electrical abnormalities in TTS are still elusive. Methods: n=32 hospitalized TTS patients and n=23 controls were analyzed. We performed cardiac magnetic resonance (CMR) with tissue mapping for the assessment of edema and interstitial expansion, global longitudinal (GLS) and circumferential strain (GCS) were evaluated by CMR feature-tracking. Twelve-lead ECGs were recorded at the time of CMR in TTS patients, aVR voltage, negative T-wave voltage and QTc length were calculated. Results: mean age of the TTS cohort was 72±12-year-old, 94% women, undergoing CMR at a median of 4 days (interquartile range 2, 6) after hospital admission. Compared with controls, patients had increased LV mass (55±11 g/m2 vs 46±8 g/m2, p<0.001), worse left ventricular ejection fraction (LVEF), GLS and GCS (all p<0.001), higher septal native T1 (1116±73 msec vs 970±23 msec, p<0.001), T2 (56±5 msec vs 46±2 msec, p<0.001) and extra-cellular volume (ECV) fraction (32±5% vs 24±1%, p<0.001). TTS patients had higher apicobasal gradient of T2 values (12±6 msec vs 2±6 msec, p<0.001), basal LV wall displayed higher native T1, T2 and ECV (all p<0.002) but similar circumferential strain against controls (-23±3% vs -24±4%, p=0.351). In the TTS cohort, septal T2 value showed significant correlations with native T1 (r=0.609, p<0.001), ECV (r=0.689, p<0.001), LVEF (r=-0.459, p=0.008) and aVR voltage (r=-0.437, p<0.05). Negative T waves voltage and QTc length significantly correlated with apicobasal T2 mapping gradient (r=0.499, p=0.007 and r=0.372, p=0.047 respectively) but not with other tissue mapping measurements. Conclusions: CMR T1 and T2 mapping demonstrated increased myocardial water content conditioning interstitial expansion in acute TTS. Myocardial edema was detected even outside areas of abnormal wall motion, its burden and distribution associated with mechanical and electrocardiographic changes, making it a potential prognostic marker and therapeutic target in TTS.